Ocean liming effect on a North Atlantic microbial community: changes in composition and rates - de Castro, Inês; Ribeiro, Susana C.; Louvado, António; Gomes, Newton Carlos Marcial; Cachão, Mário; Brito de Azevedo, Eduardo; Barcelos e Ramos, Joana (Frontiers in Marine Science, 2025)
The ongoing rise in atmospheric CO2 levels and the consequent global warming make it increasingly difficult to maintain the global temperature within the 1.5 - 2°C target set by the Paris Agreement. Therefore, strategies to remove carbon dioxide from the atmosphere are being developed, with ocean alkalinity enhancement (OAE) gaining most attention. Within OAE, ocean liming- the addition of quicklime (CaO) or hydrated lime (Ca(OH)2)- can not only remove CO2 from the atmosphere but potentially counteract the effects of ocean acidification. Although quite attractive, these technologies have yet to be tested regarding ecological safety and efficacy. Here we report the impacts of ocean liming on the abundance, composition and extracellular enzymatic activity (EEA) rates of a North Atlantic planktonic community. The results demonstrate that OAE led to a decreased phytoplankton development, mainly diatoms. The bacterial response to OAE was community-specific, with a consistent increase in the relative abundance of the order Oceanospirillales. OAE also led to increased EEA rates, especially within the bacterial community. These findings suggest that while initial effects on phytoplankton may be limited, the specific impacts on bacterial groups suggest that OAE could influence the remineralization of organic matter. If our results apply to other communities, OAE might initially affect marine microbial dynamics, but further studies are needed to determine if these effects are long-term.